Recent advances in cathode materials of rechargeable aqueous zinc-ion batteries - L. Wang (Materials Today Advances, 2020)
Given good safety, low cost, and environmental friendliness, rechargeable aqueous zinc-ion batteries (ZIBs) are considered as a more feasible solution for grid-scale applications than Li-ion batteries. The availability of suitable cathode materials to store Zn2+ is a prerequisite to realize high-performance aqueous ZIBs. However, due to the high polarization of bivalent Zn2+, Zn-host cathode materials with excellent electrochemical performances are yet to be discovered. In this review, recent advances in the cathode materials of aqueous ZIBs, including different types of cathode materials, electrode reaction mechanisms, and strategies to enhance their electrochemical performance, are briefed. Finally, current challenges and perspectives on the cathodes of ZIBs are presented.